Cytokine absorption during human kidney perfusion reduces delayed graft function–associated inflammatory gene signature. Issue 6 (22nd November 2020) - Ferdinand, John R.; Hosgood, Sarah A.; Moore, Tom; Ferro, Ashley; Ward, Christopher J.; Castro‐Dopico, Tomas; Nicholson, Michael L.; Clatworthy, Menna R.
Abstract : Transplantation is the optimal treatment for most patients with end‐stage kidney disease but organ shortage is a major challenge. Normothermic machine perfusion (NMP) has been used to recondition marginal organs; however, mechanisms by which NMP might benefit organs are not well understood. Using pairs of human kidneys obtained from the same donor, we compared the effect of NMP with that of cold storage on the global kidney transcriptome. We found that cold storage led to a global reduction in gene expression, including inflammatory pathway genes and those required for energy generation processes, such as oxidative phosphorylation (OXPHOS). In contrast, during NMP, there was marked upregulation OXPHOS genes, but also of a number of immune and inflammatory pathway genes. Using biopsies from kidneys undergoing NMP that were subsequently transplanted, we found that higher inflammatory gene expression occurred in organs with prolonged delayed graft function (DGF). Therefore, we used a hemoadsorber (HA) to remove pro‐inflammatory cytokines. This attenuated inflammatory gene expression increased OXPHOS pathway genes and had potentially clinically important effects in reducing the expression of a DGF‐associated gene signature. Together, our data suggest that adsorption of pro‐inflammatory mediators from the perfusate represents a potential intervention which may improve organ viability. Abstract : A gene signature associated with reduced delayed graft function after kidney transplantation that increases during machine normothermic perfusion further increases if cytokines are removed from the perfusate during perfusion.